Estudo de técnicas de instrumentação biomédica para aquisição de sinais musculares - Cardoso, Lucas Fernandes (Universidade Federal Rural do Semi-Árido, 2018)
Electromyography, a muscle signal generated through the variation of the cell membrane ion concentration, is of fundamental importance for the body activities, being used by several health professionals for clinical analysis. Such potentials present a series of information regarding the biological activities of the body whose capture and processing must be as accurate as possible in order to obtain good results. In order to capture this data a very used component is the amplifier of instrumentation that allows amplifying this signal allowing a better analysis of the data. However, as one of the main problems related to the amplifier is the Offset that is a voltage that is added to the signal by moving it to undesirable levels, this work aims to present some methods for reduction / elimination of Offset and other noises. These techniques will be analyzed and compared for the finality of choosing the best way to solve these problems. It was seen that the Chopper stabilization, among the presented methodologies, presented a better result, being a good choice for implementation.
Monografia
Keywords: Offset; Offset; Amplificador de Instrumentação; Instrumentation Amplifier; Biopotenciais; Biopotentials; Eletromiografia; Electromyography; ENGENHARIAS::ENGENHARIA DE COMPUTACAO